2015
DOI: 10.3354/dao02925
|View full text |Cite
|
Sign up to set email alerts
|

Cynatratoside-C efficacy against theronts of Ichthyophthirius multifiliis, and toxicity tests on grass carp and mammal blood cells

Abstract: Infection by Ichthyophthirius multifiliis, a ciliated protozoan parasite, results in high fish mortality and causes severe economic losses in aquaculture. To find new, efficient anti-I. multifiliis agents, cynatratoside-C was isolated from Cynanchum atratum by bioassay-guided fractionation in a previous study. The present study investigated the anti-theront activity, determined the toxicity of cynatratoside-C to grass carp Ctenopharyngodon idellus and mammalian blood cells, and evaluated the protection of cyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The same concentration was used for in vivo infections and showed significant treatment efficacy and protection. Furthermore, the substance was tested for toxicity to grass carp and the median lethal concentration (LC50) was found to be 46.8 mg/L and thus safe for treatment against I. multifiliis [110].…”
Section: Plant Extractsmentioning
confidence: 99%
“…The same concentration was used for in vivo infections and showed significant treatment efficacy and protection. Furthermore, the substance was tested for toxicity to grass carp and the median lethal concentration (LC50) was found to be 46.8 mg/L and thus safe for treatment against I. multifiliis [110].…”
Section: Plant Extractsmentioning
confidence: 99%
“…Chlorella vulgaris, as a beneficial algae strain with abundant nutrients which can be used by omnivorous or herbivorous animals in aquaculture, was frequently chosen as the toxicity test materials (Geiger, Hornek‐Gausterer, & Saçan, ; Najafabadi, Malekzadeh, Jalilian, Vossoughi, & Pazuki, ). Moreover, fish as a consumer of aquatic ecosystems and an important source of food is one of the closest relationships with human beings and also was used as a subject of aquatic biological toxicity test (Folmar, Sanders, & Julin, ; Fu et al, ). Bacillus subtilis has the ability to produce protease, lipase and amylase which enhances the water quality, growth performance, immune response and disease resistance in feed (Fisher, ; Zokaeifar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these protective properties of trophonts make fighting and killing them more brutal than theront and nonencysted tomonts. 12,20 The results showed that essential oils of sage at a concentration of 0.50 ml L -1 , lavender at a concentration of 0.25-and 0.50-ml L -1 , and oregano at a concentration of 0.1, 0.25-, and 0.50-ml L -1 can kill about 100% of I. multifiliis trophonts after 60 min of exposure. Further-Antiparasitic activity of medicinal plants against protozoan fish parasite Ichthyophthirius multifiliis Israeli Journal of Aquaculture -Bamidgeh more, antiparasitic efficacy correlated positively with the high concentrations of the essential oils and prolonged exposure (p<0.05).…”
Section: In Vitro Antiparasitic Efficacy Of the Essential Oilsmentioning
confidence: 99%